2018
DOI: 10.1186/s12955-018-0880-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the reliability and validity of SF-8 with a large representative sample of urban Chinese

Abstract: BackgroundThe Short Form-8 (SF-8) is a widely used instrument for measuring health-related quality of life (HRQOL). The purpose of the current study is to evaluate the reliability and validity of the Chinese version SF-8 using a large, representative sample of city residents in mainland China.MethodsWe surveyed residents of 35 major cities in China using random digit dialing of both landlines and cell phones. We adopted a multi-stage stratified sampling scheme and selected a probability sample of 10,885 adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 21 publications
9
52
0
Order By: Relevance
“…Besides this, the Spearman's correlation coefficient indicated a strong correlation of PCS and MCS with their respective domains. These results coincide with other findings, indicating that SF-8 has good reliability and correlation for measuring HRQOL [6,35,36]. Therefore, we suggest that SF-8 is a potential tool to measure health status among rural communities in Ethiopia and may contribute to cross-cultural comparison.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Besides this, the Spearman's correlation coefficient indicated a strong correlation of PCS and MCS with their respective domains. These results coincide with other findings, indicating that SF-8 has good reliability and correlation for measuring HRQOL [6,35,36]. Therefore, we suggest that SF-8 is a potential tool to measure health status among rural communities in Ethiopia and may contribute to cross-cultural comparison.…”
Section: Discussionsupporting
confidence: 90%
“…The Cronbach's α was described for the overall instrument, and a Cronbach's α coefficient of not less than 0.7 was generally considered sufficient to demonstrate internal consistency [40]. For item-total correlation, a value of >0.3 was considered to be an indicator that an item was connected to the overall scale [36]. In addition, Spearman's correlation coefficients replicated the correlation of eight dimensions and two aspects of the HRQOL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Short Form-8 (SF-8) Health Survey was conducted to measure QOL, which was derived from the Short Form-36 Health Survey. SF-8 can be completed in one to 2 mins, and can yield scores comparable to the Short Form-36 [35]. The Chinese version of SF-8 was translated and tested by Wang et al, and demonstrated good internal consistency reliability and criterion validity [35,36].…”
Section: Measurements Qolmentioning
confidence: 99%
“…SF-8 can be completed in one to 2 mins, and can yield scores comparable to the Short Form-36 [35]. The Chinese version of SF-8 was translated and tested by Wang et al, and demonstrated good internal consistency reliability and criterion validity [35,36]. Therefore, SF-8 has been applied to Chinese occupational groups [37].…”
Section: Measurements Qolmentioning
confidence: 99%